Ants of North Carolina: an updated list (Hymenoptera: Formicidae) - Guénard, Benoit; Mccaffrey, Katherine A.; Lucky, Andrea; Dunn, Rob R. (Zootaxa, 2012)
We document the distribution of ants present in North Carolina. We revisit the list of North Carolina ants for the first time since 1962, based on literature records, museum collection and new sampling events across the state. Our results show 53 new species records, including 16 exotic and 4 undescribed species, for a total of 192 species found in North Carolina. Based on our current knowledge, North Carolina possesses the highest species diversity of native ants of any state or territory in eastern North America. Here, we discuss some of the biogeographical explanations for this remarkable diversity. In addition to presenting county-level species distributions in North Carolina, we also offer brief comparisons to species lists for surrounding states. By highlighting species expected to occur in North Carolina, but not yet recorded in the state, we hope to encourage new discoveries and increase the general knowledge of the ant fauna of North Carolina.